Relationship between Mother's Knowledge of Feeding Patterns and Nutritional Status of 1-3 Years Old Children at Hugo Hasena Tanjung Pura Clinic, Langkat Regency - Setia Sihombing; Miranti; Siti Sundari (Institute of Computer Science (IOCS), 2019)
The period of rapid growth occurs in infancy and toddlerhood. Therefore, at this time good and sufficient nutrition is needed for babies (Raharjo, 2014). Based on the results of the 2018 Ministry of Health Basic Health Research, 17.7% of infants under 5 years old (toddlers) still experience nutritional problems. This figure consists of toddlers who experience malnutrition by 3.9% and those who suffer from malnutrition by 13.8% (Kemenkes RI, 2018). The purpose of the study was to identify the frequency distribution of Mother's Knowledge About Feeding Patterns for Children aged 1-3 Years at the Hugo Hasena Tanjung Pura Clinic, Langkat Regency in 2019. The research design used was an analytical survey (Explanatory Research) with a cross-sectional approach. The research sample was all mothers who had children aged 1-3 years at Hugo Hasena Clinic, as many as 34 people. Collecting data using primary data obtained directly from mothers who have children aged 1-3 years through a questionnaire. The data were analyzed by chi-square, at the limit of the statistical significance of the calculation of p value (0.05). The results showed that there was a significant relationship between mother's knowledge about feeding patterns and the nutritional status of children aged 1-3 years with a p value of 0.000 (<0.05). It was concluded that there was a significant relationship between mother's knowledge about feeding patterns and the nutritional status of children aged 1-3 years at the Hugo Hasena Tanjung Pura Clinic, Langkat Regency in 2019